Density measurement, tensile, and morphology properties of polylactic acid biocomposites foam reinforced with different kenaf filler loading - Nur Adilah Abu Hassan,; Sahrim Ahmad,; Ruey, Shan Chen (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper investigates the performance of polylactic acid (PLA)/kenaf fiber (KF) composites foamed using azodicarbonamide (AC) in terms of density, mechanical, and morphology aspects. The KF loading was varied in the range of 20-40 wt. %. The mixtures were compounded using a co-rotating twin-screw extruder and followed by hotcold pressing in order to prepare test specimens for characterization. The density of the foamed composites showed a fluctuate trend where it decreased at lower KF loading (0-20 wt. %) while further increasing fiber loading (30-40 wt. %) resulted in an increase of the composites density. Tensile results showed that the optimum loading of KF was achieved at 30 wt. % with an improvement of 135, 153, and 27.6% for stress at yield, strain at break and Young modulus, respectively, as compared to neat PLA foam. Field emission scanning electron microscope (FESEM) micrographs confirmed the fiber dispersion and morphological interaction between PLA and KF components.